2007
DOI: 10.1111/j.1467-6486.2006.00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Don't Take It Personally: Exploring Cognitive Conflict as a Mediator of Affective Conflict

Abstract: Research has sought to explain the multi-dimensionality of conflict and its paradoxical effects on decision making (Amason, 1996; DeDreu and Weingart, 2003; Jehn, 1995). The primary prescription to emerge from this work has been for teams to seek the benefits of cognitive (task) conflict while simultaneously avoiding the costs of affective (emotional) conflict. The problem is that these two types of conflict often occur together and researchers have offered few explanations as to why this happens or guidance a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
249
1
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 222 publications
(275 citation statements)
references
References 69 publications
(170 reference statements)
8
249
1
17
Order By: Relevance
“…This finding adds to the growing stream in conflict research which investigates boundary conditions of the association between task and relationship conflicts. Prior investigations have demonstrated the quality of interpersonal relationships in a team to be important for the link between task and relationship conflicts (Mooney et al, 2007;Simons & Peterson, 2000). Collective team identification, however, goes beyond relationship quality in that it includes strong emotional ties and a feeling of common belonging among team members (Ashforth et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This finding adds to the growing stream in conflict research which investigates boundary conditions of the association between task and relationship conflicts. Prior investigations have demonstrated the quality of interpersonal relationships in a team to be important for the link between task and relationship conflicts (Mooney et al, 2007;Simons & Peterson, 2000). Collective team identification, however, goes beyond relationship quality in that it includes strong emotional ties and a feeling of common belonging among team members (Ashforth et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the positive potential of task-related conflicts to benefit team performance is at risk of being jeopardized by performance-impeding relationship conflicts. While prior studies have identified boundary conditions which attenuated the association between the two conflict types, they did not succeed in completely resolving the dilemmatic association (Greer et al, 2008;Mooney et al, 2007;Simons & Peterson, 2000). The purpose of this study was to scrutinize the promise of both collective team identification and team member alignment (i.e., the existence of shared team goals and team-based rewards) for separating task and relationship conflicts in teams.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations